Animated Video Development in Thematic Learning in the Fifth Grade of Elementary School - Faujiah, Erika; Nulhakim, Lukman; Hendracipta, Nana (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Thematic learning for elementary students is challenging since combining many subjects matter in one topic so the appropriate medium to deliver the subject should be taken into consideration. This study aims to develop animated videos in fifth grade at SDN Cijeruk and determine the video’s feasibility and student responses after using the video. The background of this research is that the teacher only used the lecture method and textbooks, making students feel bored and sleepy. In addition, teachers did not make good use of school facilities with laptops, InFocus, and speakers to apply digital learning media. Teachers also did not make use of their soft skills in using technology. This research method was RD (Research and Development) using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The results of the material expert validation from the two validators obtained an average percentage of 89.5%, on the criteria of